Analisis Keefektivitasan Penggunaan Media Pembelajaran Tradisional Dan Modern Menurut Pandangan Mahasiswa Program Studi Pendidikan - Kiky Zakiya Ramadhani Dalimunte; Meysa Nur Sabrina; Natasha Aliyan Kusdian; Sifa Fauziah (STIKes Ibnu Sina Ajibarang, 2024)
Media learning is an integral part of the modern educational process which make a significant contribution to the effectiveness of learning and also provides a means of facilitating effective and interesting learning for students. Along with technological developments, media learning has undergone a significant transformation, from traditional to modern using advanced technology. The debate about the effectiveness between traditional and modern media learning continues to be a concern in the world of education. The effectiveness of media learning is an important instrument in supporting the achievement of learning objectives. Quantitative methods are used by researchers to obtain accurate information that is based on empirical phenomena and can be measured. The aim of this research is to determine the effectiveness of traditional and modern media learning in implementing student learning activities. The quantitative sample consists of 100 students selected randomly from each population stratum. The quantitative sample consists of students selected purposively based on certain criteria.